Transfer Pricing Sektor Pertambangan: Moderasi Good Corporate Governance - Nurmalitasari, Indah; Wulandari, Sartika (Gorontalo Accounting Journal, 2025)
The aim of this study is to analyze and test the effects of tax minimization, exchange rate, and tunneling incentive on the decisions of mining companies to implement transfer pricing, with good corporate governance (GCG) as a moderating variable. The sample consists of 103 mining companies that reported complete financial statements during the period of 2018-2022, selected using purposive sampling. Hypothesis testing was performed using Eviews 12 software. The results indicate that tunneling incentive, moderated by GCG, has a significant effect on transfer pricing decisions. Meanwhile, the tax minimization variable, moderated by GCG, does not have a significant effect on transfer pricing decisions. Partially, tunneling incentive has a significant impact on transfer pricing, while tax minimization and exchange rate do not show a significant effect on transfer pricing decisions.